Drug-induced Sleep Endoscopy: Are there Predictors for Failure of Oral Appliance Treatment? - Veugen, Christianne C. A. F. M.; Sanders, Rineke M. C.; Stokroos, Robert J.; Copper, Marcel P. (International Archives of Otorhinolaryngology, 2021)
Introduction In the literature, evidence is lacking on the predictive value of drug-induced sleep endoscopy (DISE) for oral appliance treatment (OAT).Objectives The aim of the present study is to evaluate whether DISE with concomitant mandibular advancement maneuver can predict failure of OAT.Methods An observational retrospective study including patients diagnosed with obstructive sleep apnea (OSA) who previously received OAT. Results of DISE were analyzed in a group with documented OAT failure (apnea-hypopnea index [AHI] > 10 events/hour or < 50% reduction) and a group with OAT benefit (AHI <10 events/hour or > 50% reduction). The upper airway was assessed using the velum, oropharynx, tongue base, epiglottis (VOTE) classification. Additionally, a mandibular advancement maneuver, manually protruding the mandible by performing a jaw thrust, was performed to mimic the effect of OAT.Results The present study included 50 patients with OAT failure and 20 patients with OAT benefit. A subgroup analysis of patients with OAT failure and an AHI < 30 events/hour included 26 patients. In the OAT failure group, 74% had a negative jaw thrust maneuver. In the subgroup with an AHI < 30 events/hour, 76.9% had a negative jaw thrust maneuver. In the OAT benefit group, 25% had a negative jaw thrust maneuver (p < 0.001).Conclusions A negative jaw thrust maneuver during DISE can be a valuable predictor for OAT failure, independent of AHI. Drug-induced sleep endoscopy should be considered as a diagnostic evaluation tool before starting OAT.
Keywords: obstructive sleep apnea; drug-induced sleep endoscopy; oral appliance treatment; mandibular advancement device; treatment outcome prediction